2007
DOI: 10.1038/sj.bjc.6603621
|View full text |Cite
|
Sign up to set email alerts
|

Widening socio-economic inequalities in oral cancer incidence in Scotland, 1976–2002

Abstract: Oral cancer incidence was investigated among 10 857 individuals using Scottish Cancer Registry data. Since 1980 the incidence of oral cancer among males in Scotland has significantly increased, the rise occurring almost entirely in the most deprived areas of residence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
1
27
0
2
Order By: Relevance
“…The study recruited incident cases from the Glasgow population and because head and neck cancers are more prevalent in the lower social groups [28,29] more cases were from deprived areas compared to the population. Randomly sampled from cases' GP practice lists (matched only for age and sex), the overall control group was more deprived than the Glasgow population.…”
Section: Discussionmentioning
confidence: 99%
“…The study recruited incident cases from the Glasgow population and because head and neck cancers are more prevalent in the lower social groups [28,29] more cases were from deprived areas compared to the population. Randomly sampled from cases' GP practice lists (matched only for age and sex), the overall control group was more deprived than the Glasgow population.…”
Section: Discussionmentioning
confidence: 99%
“…Trends in skin cancer incidence in Scotland VR Doherty et al category 5 : 1 ratio over a similar time period (Conway et al, 2007). In oral cancer, in which smoking is an accepted risk factor, the change was more marked in males and the decline of smoking in the less deprived groups was considered to have contributed.…”
Section: Discussionmentioning
confidence: 99%
“…The Carstairs deprivation index is based on small area of residence, and is derived from four variables collected at each decennial census: social class, unemployment, overcrowding and car ownership (Morris and Carstairs, 1991). Previous work has shown that, when studying trends in socioeconomic inequalities since the mid-1970s, the use of the 1981, 1991 and 2001 Carstairs scores applied to successive time periods provides similar results to the use of the 1991 index on its own (Conway et al, 2007). Midyear population estimates were obtained from the General Register Office for Scotland (Registrar General for Scotland, 1979Scotland, -2005.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 There are a multitude of factors involved in the prognosis of oral cancer and probably no single marker can accurately predict the outcome. 11 Some studies have investigated OSCC in women, 7,[14][15][16][17] although little is known about survival and prognostic factors, mainly because of the small sizes of the samples studied. Therefore, whether there are gender differences in prognostic factors remains an unanswered question.…”
mentioning
confidence: 99%